Salmonellosis in adult cattle in Central Argentina: case series - Azaldegui, Ignacio; Fiorentino, María Andrea; Morrell, Eleonora Lidia; Odriozola, Ernesto Raul; Garcia, Juan Agustin; Canton, German Jose (Springer, 2024)
Salmonellosis is an infectious disease caused by bacteria belonging to the Salmonella genus. Bovine salmonellosis is more frequent in young cattle under intensive overcrowd husbandry conditions, and therefore uncommon in adults. We report four outbreaks of clinical salmonellosis due to Salmonella Typhimurium, Salmonella Newport and Salmonella Dublin provoking outbreaks of diarrheic/septicemic disease in adult cattle of Central Argentina. Anamnesis information, clinical, pathological, and bacteriological findings were retrospective analyzed. This report emphasizes the importance to include salmonellosis among the differential diagnosis of clinical enteric/septicemic disease in adult cattle under different husbandry conditions in Argentina. The source of Salmonella could not be established in these outbreaks.